Inverted Bulk‐Heterojunction Solar Cells using Polyethylenimine‐Ethoxylated Processed from a Fully Aqueous Dispersion as Electron‐Transport Layer. Issue 11 (28th October 2015) - Polino, Giuseppina; Casaluci, Simone; Dianetti, Martina; Dell'Elce, Simone; Liscio, Andrea; Mirruzzo, Valentina; Cardone, Giorgio; Susanna, Gianpaolo; Salamandra, Luigi; Brown, Thomas M.; Reale, Andrea; Di Carlo, Aldo; et al.
Abstract: In this work, we present the realization and characterization of bulk‐heterojunction (BHJ) solar cells in which we use a spin‐coated polyethylenimine‐ethoxylated (PEIE) layer as electron‐transporting layer deposited from a fully water‐based solution. We investigated several concentrations of PEIE in aqueous solution and characterized the chemical and electrical behavior of PEIE‐coated fluorinated tin oxide (FTO) substrates. We realized BHJ solar cells using P3HT:PC60 BM as active layer achieving a maximum efficiency of 4 % that outperform the device fabricated using a 2‐methoxyethanol‐based PEIE solution considered as reference. Moreover, devices fabricated with the water‐based PEIE solution showed a higher shelf‐life stability compared to those made with the 2‐methoxyethanol‐based PEIE solution. The performances of the devices realized with the water‐based solution were characterized over a period of more than 6 months showing a decrease of 30 % in efficiency. Abstract : The incredible bulk: We realized bulk‐heterojunction (BHJ) solar cells using P3HT:PCBM as active layer and polyethylenimine‐ethoxylated (PEIE) caste from aqueous solution and achieved high efficiency, outperforming the device fabricated using the 2‐methoxyethanol‐based PEIE solution processing considered as reference. The devices realized using water‐based PEIE solution also showed a higher shelf‐life stability compared to the one made with 2‐methoxyethanol‐based PEIE solution.